2005
DOI: 10.1016/j.ydbio.2004.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus p21-activated kinase 5 regulates blastomeres' adhesive properties during convergent extension movements

Abstract: The p21-activated kinase (PAK) proteins regulate many cellular events including cell cycle progression, cell death and survival, and cytoskeleton rearrangements. We previously identified X-PAK5 that binds the actin and microtubule networks, and could potentially regulate their coordinated dynamics during cell motility. In this study, we investigated the functional importance of this kinase during gastrulation in Xenopus. X-PAK5 is mainly expressed in regions of the embryo that undergo extensive cell movements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 90 publications
3
26
1
Order By: Relevance
“…We found that PAK4, PAK5 and PAK6 all target to cell-cell adhesions to varying degrees, indicating cell-cell adhesion targeting is not unique to PAK6 among the PAK family, but is a characteristic of type II PAKs. This is in agreement with previously published work showing that type II PAKs from other species, Xenopus PAK5 and Drosophila Mbt, also target to cell-cell adhesions (Schneeberger and Raabe, 2003;Faure et al, 2005). Further, while this manuscript was in preparation, a study was published confirming our observations that GFP-PAK4 localizes weakly to cell-cell adhesions (Selamat et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that PAK4, PAK5 and PAK6 all target to cell-cell adhesions to varying degrees, indicating cell-cell adhesion targeting is not unique to PAK6 among the PAK family, but is a characteristic of type II PAKs. This is in agreement with previously published work showing that type II PAKs from other species, Xenopus PAK5 and Drosophila Mbt, also target to cell-cell adhesions (Schneeberger and Raabe, 2003;Faure et al, 2005). Further, while this manuscript was in preparation, a study was published confirming our observations that GFP-PAK4 localizes weakly to cell-cell adhesions (Selamat et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…In keeping with this, we found that PAK6 constructs with altered catalytic activity (kinase-dead K436M, hyperactive P52L) but with intact N-termini still localize at cell-cell adhesions, indicating that PAK6 targeting to cell-cell adhesions is independent of catalytic activity. In agreement with our findings, the Xenopus type II PAK, PAK5 (also known as PAK7), targets to cell-cell junctions independent of catalytic activity (Faure et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Knockdown of Inca expression by antisense morpholino oligonucleotides (MOs) in both Xenopus and zebrafish results in dramatic reductions in cranial NC-derived cartilage formation. We show that Inca interacts with PAK5, a p21-activated kinase downstream of the Rho GTPases Cdc42 and Rac1, previously implicated in cytoskeletal organization and apoptosis (Bokoch, 2003;Jaffer and Chernoff, 2002) as well as control of cell adhesion and convergent extension movements in Xenopus (Cau et al, 2001;Faure et al, 2005). Consistent with a role in cytoskeletal organization, Inca overexpression disrupts both cortical pigmentation in blastomeres and wound healing in Xenopus embryos.…”
Section: Introductionsupporting
confidence: 55%
“…Xenopus PAK5 is expressed maternally and, by the gastrula stages, expression overlaps that of Inca in the ectoderm, although it is not restricted to the inner, sensorial layer (Faure et al, 2005). At later stages, PAK5 expression appears ubiquitous (Fig.…”
Section: Inca Modulates Cytoskeletal Dynamics In Association With Pak5mentioning
confidence: 98%
See 1 more Smart Citation